Comparative socio-political attitudes 1979-1980 - Ekehammar, Bo (Stockholm University, 2010)
This study is an international expansion of the Socio-political attitudes 1979 study. Youths in the United States and Australia have answered the same questions as the Swedish youths. The aim is to compare different countries in regard to political socialization, political perception/cognition and social attitudes.

This study is an international expansion of the Socio-political attitudes 1979 study. Youths in the United States and Australia have answered the same questions as the Swedish youths. The aim is to compare different countries in regard to political socialization, political perception/cognition and social attitudes.
Komparativa sociopolitiska attityder 1979-1980
Keywords: Political behaviour and attitudes; Politiska beteenden och attityder; Youth; Ungdomar; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap